Organisational change, absenteeism and welfare dependency - Knut Røed; Elisabeth Fevang (University of Oslo, Department of Economics, 2005)
We show that recent attempts to reorganise and cut costs in the Norwegian health care and social services sectors have had the unintended side effects of raising the level of sickness absence and disability among the employees, and that these effects have persisted several years after completion of the reorganisation processes. Since a substantial proportion of the resulting costs are external to the decision-makers, we suspect that the pace of change may have been excessively high. Changes that were efficient from each service provider's point of view may have been inefficient from a social and a public-finance point of view.
Keywords: C14; I38; J28; 330; Absenteeism; hazard rate model; NPMLE; Organisatorischer Wandel; Arbeitsbedingungen; Pflegeberufe; Fehlzeit; Moral Hazard; Norwegen